Chapter 2 Fighting Avant-Garde with Phenomenology Gustav Shpet's 'New Realism' - Bourgeot, Liisa (Taylor & Francis, 2023)
The article discusses Gustav Shpet's phenomenology and aesthetic theory as part of early Soviet culture. The author suggests that the 'official' acceptance of Shpet's philosophy, particularly through GAKhN, is emblematic of the internal complexity of the cultural regime in the 1920s. Shpet's pre-revolutionary phenomenology was praised for its modernizing potential, while his later anti-avant-garde art theory was criticized as old-fashioned and unscientific. Yet both were welcomed by Marxist thinkers and the Bolshevik regime. Shpet's involvement in Soviet culture from 1917 to 1929 can thus be seen as a reflection of its gradually changing needs. His aesthetics of 'new realism' and the 'inner form of the word' were deemed useful until the end of the 1920s, when he was finally charged with 'idealism' and 'anti-communism'. Nonetheless, Shpet's neo-classical cultural conception can be considered part of a broad conservative turn that eventually led to the introduction of socialist realism.